Dental Implants Loaded With Bioactive Agents Promote Osseointegration in Osteoporosis: A Review - Zhang, Cheng; Zhang, Tianjia; Geng, Tengyu; Wang, Xudong; Lin, Kaili; Wang, Penglai (Frontiers in Bioengineering and Biotechnology, 2021)
Implant-supported dentures are widely used in patients with defect or loss of dentition because these have higher chewing efficiency and do not damage the adjacent teeth compared with fixed or removable denture. An implant-supported denture carries the risk of failure in some systemic diseases, including osteoporosis, because of a non-ideal local microenvironment. Clinically common physical and chemical modifications are used to change the roughness of the implant surface to promote osseointegration, but they have limitations in promoting osteoinduction and inhibiting bone resorption. Recently, many researchers have focused on the study of bioactive modification of implants and have achieved promising results. Herein we have summarized the progress in bioactive modification strategy to promote osseointegration by regulating the local osteoporotic microenvironment.